Trust in the Internet as a Health Resource Among Older Adults: Analysis of Data from a Nationally Representative Survey - Zulman, Donna M; Kirch, Matthias; Zheng, Kai; An, Lawrence C (JMIR Publications, 2011)
BackgroundDistrust in the Internet as a source of health information remains common among older adults. The influence of this distrust on Internet use for health-related purposes, however, is unclear. ObjectiveThe objective of our study was to explore how older adults' trust in the Internet influences their online health-related activities, and to identify potential targets for improving health-related Internet resources for older adults. MethodsData were obtained from a nationally representative, random digit-dial telephone survey of 1450 adults 50 years of age and older in the United States. A model was developed to conceptualize the hypothesized relationships among individual characteristics, distrust, and avoidance of the Internet as a health resource. Multivariate logistic regression analyses were conducted to examine the association between trust in online health information and use of the Internet for health-related purposes. Additional multivariate logistic regression analyses were conducted to identify the key characteristics associated with trust in online health information, adding sequentially the variables hypothesized to account for distrust among older adults: sociodemographic and health characteristics, inexperience and technical difficulties with the Internet, negative feelings toward the Internet, and lack of awareness about the sources providing the health information found online. ResultsThe mean (SD) age of the study population was 63.7 (10.6) years. Of the 823 (56.8%) Internet users, 628 (76.3%) reported using the Internet as a health resource. Trust in the Internet as a source of health information was associated with using the Internet for a number of health activities, including searching for information about a specific health condition (adjusted OR 4.43, P < .001), purchasing prescription drugs (adjusted OR 2.61, P = .03), and talking with a health care provider about information found online (adjusted OR 2.54, P = .002). Older adults (age ≥65 years) were less likely to trust the Internet as a source of health information (OR 0.63, P = .04), even after adjusting for other sociodemographic characteristics and health and function. This age effect was only slightly attenuated (adjusted OR 0.69, P = .13) after adjusting for inexperience and technical difficulties with the Internet, but it disappeared entirely (adjusted OR 0.96, P = .91) after adjusting for other hypothesized contributors to distrust (including finding the Internet confusing because it provides "too much information," and lacking awareness about the source providing health information found online). ConclusionsWebsite design features that clearly identify the source and credibility of information and minimize confusion may build trust among older adults and offer an opportunity to increase the utility of the Internet as a health resource for this population.